Gilgamesz : powiesc starobabilonska - Wittlin, Jozef, 1896-1976.; Zulawski, Marek (Warszawa : Panstwowy Instytut Wydawniczy, 1986)
A story from Ancient Babylon.
Translation of Gilgamesh.
Keywords: Iraq -- History -- To 634 -- Fiction